Predicting Creative Teaching Skills of Faculty Members Teaching Science through their Multiple Level of Intelligence at Umm Al-Qura University - Alnajjar , Eiad (Dirasat: Educational Sciences, 2021)
This study aims to predict creative teaching skills of science faculty members through the level of multiple intelligences they have at Umm Al-Qura University. The study sample consisted of all science faculty members at Al-Qunfudhah University College at Umm Al-Qura University, and their number was (24) faculty members in all science disciplines. To collect data, a tool was prepared to survey the nine multiple intelligences to suit Saudi environment, and a questionnaire was used to measure the extent to which science faculty members possess creative teaching skills with their students. The study concluded that the average multiple intelligences of science faculty members were logical, existential, subjective, verbal, social, visual, natural, physical, and finally musical intelligence. It also showed that most of science faculty (58%) had good creative teaching skills. As for the remaining (42%), they possessed creative teaching to a great exent. The study recommends encouraging science faculty members and inviting them to practice teaching strategies that contribute to the development of creativity and creative thinking.